2021
DOI: 10.3390/jcm10030542
|View full text |Cite
|
Sign up to set email alerts
|

High Agreement between Barrett Universal II Calculations with and without Utilization of Optional Biometry Parameters

Abstract: Purpose: To examine the contribution of anterior chamber depth (ACD), lens thickness (LT), and white-to-white (WTW) measurements to intraocular lens (IOL) power calculations using the Barrett Universal II (BUII) formula. Methods: Measurements taken with the IOLMaster 700 (Carl Zeiss, Meditec AG, Jena, Germany) swept-source biometry of 501 right eyes of 501 consecutive patients undergoing cataract extraction surgery between January 2019 and March 2020 were reviewed. IOL power was calculated using the BUII formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Hyperopic shift is associated with a thicker lens, while a myopic shift is associated with a thin lens, especially for the Haigis formula which did not include LT [19,25,44]. Even for formulas that included LT, the effect of LT on refractive error is varied with different ALs, with the greatest effect seen in eyes with AL less than 22 mm [18]. Besides, there is a positive correlation between LT and postoperative IOL position as demonstrated in previous studies [3,26].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Hyperopic shift is associated with a thicker lens, while a myopic shift is associated with a thin lens, especially for the Haigis formula which did not include LT [19,25,44]. Even for formulas that included LT, the effect of LT on refractive error is varied with different ALs, with the greatest effect seen in eyes with AL less than 22 mm [18]. Besides, there is a positive correlation between LT and postoperative IOL position as demonstrated in previous studies [3,26].…”
Section: Discussionmentioning
confidence: 65%
“…Longer AL is associated with higher central cornea thickness (CCT), higher corneal radius, larger corneal diameter and deeper anterior chamber depth (ACD) in normal eyes [13][14][15], but these correlations may be not present in eyes with extreme long or short AL [16,17]. Vega et al found that the effect of LT on the accuracy of the Barrett Universal II formula was the greatest in eyes with AL ≤ 22 mm but less in eyes with AL ≥ 26 mm [18]. Even among patients with normal ALs (22-26 mm), a higher prediction error may be seen with an extreme LT, especially for the Haigis and Hill-RBF V2.0 formulas [19].…”
Section: Introductionmentioning
confidence: 99%
“…In general, it is difficult to check the performance of different formulae, as it is mostly dependent on the composition of the dataset, and there are no common rules on how to evaluate the performance. Therefore, some formulae are superior in long or short eyes [ 11 , 12 ], or in eyes with a steeper or flatter cornea, or selected combinations of axial length and corneal curvature. Additionally, the performance of a formula mostly depends on the dataset used for constant optimization as well as the technique applied for optimizing the constants, and it can also depend on the biometer settings, quality of the clinical measurement data (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, BUII formula, not included in the IOLMaster 500, was analyzed. Although ACD knowledge was recommended also for BUII formula, together with other optional parameters, it is possible to use this formula even without this information 30 , 31 . On the other hand, it was not possible to include other fourth-generation IOL power calculation formulas due to the necessity to know the ACD measurements to work reliably 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%